Acculturation and School Adjustment of Immigrant Youth in Six European Countries: Findings from the Programme for International Student Assessment (PISA) - Schachner, Maja K.; He, Jia; Heizmann, Boris; Van de Vijver, Fons J. R. (Frontiers in Psychology, 2017)
School adjustment determines long-term adjustment in society. Yet, immigrant youth do better in some countries than in others. Drawing on acculturation research (Berry, 1997; Ward, 2001) and self-determination theory (Ryan & Deci, 2000), we investigated indirect effects of adolescent immigrants’ acculturation orientations on school adjustment (school-related attitudes, truancy, mathematics achievement) through school belonging. Analyses were based on data from the Programme for International Student Assessment (PISA) from six European countries, which were combined into three clusters based on their migrant integration and multicultural policies: Those with the most supportive policies (Belgium and Finland), those with moderately supportive policies (Italy and Portugal), and those with the most unsupportive policies (Denmark and Slovenia). In a multigroup path model, we confirmed most associations. As expected, mainstream orientation predicted higher belonging and better outcomes in all clusters, whereas the added value of students’ ethnic orientation was only observed in some clusters. Results are discussed in terms of differences in acculturative climate and policies between countries of settlement.